Farmers Commitment in Maintaining Wetted land Ownership Status in Peri-Urban Area of Yogyakarta - Sudrajat sudrajat (Indonesian Journal of Geography, 2016)
The existance of wetted land in Peri-urban Yogyakarta can not separated from the farmer’s commitment. This research is aimed to analyze farmer’s commitment in maintaining wetted land ownership status in Peri-Urban Yogyakarta and to identify its influencing factors. This research is conducted in peri-urban area of Yogyakarta by taking some wettted land’s owners who are active in farming, as the respondents. The meaurement of farmer’s commitment indicators are done by likert scale. The result indicated that farmers in Peri-urban area of Yogyakarta have low commitment in maintaining wetted land ownership status.  Low level of farmer’s commitment are reflected from the low commitment to prevent the desire to sell the wetted land,  to rent out the wetted land for non-agricultural use and to change the wetted land for non-agricultural use. This research also indicated that the low commitment is also significantly influenced by wetted land price, wetted land location, and its social value.